Pola Interaksi Sosial Ibu Rumah Tangga Pengguna Media Sosial Facebook di Kelurahan Partali Toruan Kecamatan Tarutung Tahun 2025 - Wediawati Simanjuntak; Sudirman Lase; Roida Lumbantobing; Harisan Boni Firmando; Masniar Hernawati Sitorus (Pusat Riset dan Inovasi Nasional, 2025)
Does the presence of Facebook social media make changes in interactions, which are usually active housewives gossiping (light discussions) on the porch of the house, after the presence of Facebook social media, housewives choose to interact online rather than face to face. This research was conducted in Partali Toruan Village using qualitative research methods and informants who became informants were housewives in Partali Toruan Village. Data collection techniques were carried out by observation, interviews, documentation and drawing conclusions. The results of the study indicate that Facebook has an impact on changes in interaction patterns in mothers in Partali Toruan Village, North Tapanuli Regency and these changes are planned changes or come from one's own will. Meanwhile, the conclusions based on the researcher's sub-problems are as follows: Most of the core of the negative impact of Facebook on changes in interaction patterns with family and the Partali Toruan community environment on mothers in Partali Toruan Village, North Tapanuli Regency is making Facebook social media a money field, namely by selling online, and eliminating boredom. Facebook has a negative impact if its users misuse Facebook as a life regulator.